Cover Image. Issue 4 (1st April 2021) - Hsu, Ya‐Chieh; Rendl, Michael
Abstract : The cover image is based on the Editorial Skin stem cells in health and in disease by Ya‐Chieh Hsu and Michael Rendl. https://doi.org/10.1111/exd.14318 .